La normalisation financière internationale face à l’émergence de nouvelles autorités épistémiques américaines - Grégory Vanel (Revue de la Régulation)
International financial normalization and U.S. epistemic authorities: the case of rating agencies, accounting and prudential norms. Financial services industry is in great transformation for the last two decades. National financial structures, national financial systems and the international financial system have been profoundly altered. Normative frameworks have also been changed, especially the way to estimate the profitability of economic activities. This trend can be explained by using a conception of hegemony which emphasize on legitimacy of day-by-day practices. In particular, we can see the emergence and the institutionalisation of U.S. epistemic authorities, sometimes called hybrids, in the world financial services industry, notably concerning accounting norms, rating activities and banking prudential norms. Whether no general neo-liberal norm was strongly imposed around the world, financialization of capitalism can nonetheless be seen as a deep spread of U.S. financial schemes and practices. However, this projection of U.S. financial practices around the world causes lots of problems and is contested, in part because of contradictions, so that these epistemic authorities always try to strengthen their legitimacy.